Anti-arthritic actions of relaxin, in combination with estrogens, in joint and bone tissue - Bagnell, Carol A.; Santora, Karen; Ho, Teh-Yuan (Italian Journal of Anatomy and Embryology, 2014)
The incidence and severity of rheumatoid arthritis decline during pregnancy. However, the role of hormones of pregnancy, including estrogens and relaxin, in attenuating the symptoms of rheumatoid arthritis, including joint inflammation and bone destruction is unknown. In rat adjuvant-induced arthritis, a model for rheumatoid arthritis, relaxin in combination with estrogens, reduced joint inflammation and circulating levels of pro-inflammatory, tumor necrosis factor α. In addition, relaxin together with estrogens, altered systemic levels of bone remodeling markers receptor activator of nuclear factor-kappa B, its ligand and osteoprotegerin to improve bone health when compared with arthritic controls. In vitro studies using primary rat osteoblasts and an osteoblast cell line showed a similar bon-saving response to treatment with estrogens in combination with relaxin.